2013
DOI: 10.2337/dc12-1276
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver Increases the Association of Metabolic Syndrome With Diabetes and Atherosclerosis

Abstract: OBJECTIVETo analyze the participation of fatty liver (FL) in the association of metabolic syndrome (MS) with type 2 diabetes and coronary artery calcification (CAC).RESEARCH DESIGN AND METHODSA total of 765 subjects (52% women) aged 30 to 75 years without clinical atherosclerosis were included in this study. MS was defined in accordance with the Adult Treatment Panel III (ATPIII) guidelines, while FL and CAC were identified by computed tomography.RESULTSThere were increasing frequencies of type 2 diabetes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…950 951 952 953 954 955 956 957 958 959 960 961 962 963 964 965 966 967 968 969 970 971 972 973 974 975 976 977 978 979 980 981 982 983 984 985 986 987 988 989 990 991 992 993 994 995 996 997 998 999 1000 1001 1002 1003 1004 considered the hepatic manifestation of MetS (158,159). We recently reported that fatty liver increases the strength of association of MetS with T2DM and that subjects with both diagnoses (MetS and fatty liver) had a higher independent risk of subclinical CAD (160). Moreover, large crosssectional epidemiological studies have shown that although VAT is the strongest correlate of fatty liver, liver fat content remains associated with dyslipidemia, abnormal blood glucose, and CAD, even after adjusting for VAT (159,161,162).…”
Section: Fatty Liver and Metabolic Syndrome: Cause Or Effect?mentioning
confidence: 96%
“…950 951 952 953 954 955 956 957 958 959 960 961 962 963 964 965 966 967 968 969 970 971 972 973 974 975 976 977 978 979 980 981 982 983 984 985 986 987 988 989 990 991 992 993 994 995 996 997 998 999 1000 1001 1002 1003 1004 considered the hepatic manifestation of MetS (158,159). We recently reported that fatty liver increases the strength of association of MetS with T2DM and that subjects with both diagnoses (MetS and fatty liver) had a higher independent risk of subclinical CAD (160). Moreover, large crosssectional epidemiological studies have shown that although VAT is the strongest correlate of fatty liver, liver fat content remains associated with dyslipidemia, abnormal blood glucose, and CAD, even after adjusting for VAT (159,161,162).…”
Section: Fatty Liver and Metabolic Syndrome: Cause Or Effect?mentioning
confidence: 96%
“…It has been proposed that the well-evidenced pathogenic relationship between hyperferritinemia and the metabolic syndrome is mediated by undiagnosed hepatosteatosis [80] which in turn exacerbates the association between this condition and increased risk for DM Ⅱ and atherosclerotic disease [81] . Up to 30% of NAFLD patients present with baseline hyperferritinemia [82] considered a reliable predictive marker for NASH, validating its incorporation into the NAFIC score shown to outperform both the HAIR score and Gholam's model [83] .…”
Section: Iron Parametersmentioning
confidence: 99%
“…A previous cross-sectional study showed that the combination of NAFLD and MetS is associated with higher prevalence of diabetes [12]. However, little is known about the combined effect of fatty liver and MetS on incident type 2 diabetes.…”
mentioning
confidence: 99%